2020
DOI: 10.14710/ik.ijms.25.1.23-30
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasite Prevalences of Grouper Fish (Epinephelus fuscogutatus x Epinephelus polyphekadion) Cultured in Floating Net Cages

Abstract: Monitoring the health of the reared fish in a floating net cage (FNC) is often conducted by examining their ectoparasites. This study determines ectoparasite prevalences of grouper fish (Epinephelus fuscogutatus x E. polyphekadion). It was conducted in the waters surrounding Pongok Island, South Bangka Regency. The health examination of both fish and ectoparasites was carried out by applying simple random sampling during three periods, November 2016 (I), February 2017 (II) and May 2017 (III). Hydro-oceanograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The value of heavy metals (Pb) in grouper meat of 6,500 mg.L -1 indicates that this value is far above the quality standard threshold value of 0.050 mg.L -1 with a difference of 6,450 mg.L -1 above the quality standard, it is suspected that grouper may have experienced biomagnification from the food he ate (Adibrata et al, 2013), found heavy metal concentrations (Pb and Cu) in fish and shellfish (Arifin, 2011). Besides, the presence of fish parasites such as ectoparasites attached to the fish skins of floating net cage systems (KJA) is thought to be related to the hydro-oceanographic dynamics such as current conditions and water temperatures (Adibrata et al, 2020). The weaker water currents and the lower the water temperature can increase ectoparasites against fish in floating cage, this is certainly very detrimental to grouper fish farmers.…”
Section: Resultsmentioning
confidence: 99%
“…The value of heavy metals (Pb) in grouper meat of 6,500 mg.L -1 indicates that this value is far above the quality standard threshold value of 0.050 mg.L -1 with a difference of 6,450 mg.L -1 above the quality standard, it is suspected that grouper may have experienced biomagnification from the food he ate (Adibrata et al, 2013), found heavy metal concentrations (Pb and Cu) in fish and shellfish (Arifin, 2011). Besides, the presence of fish parasites such as ectoparasites attached to the fish skins of floating net cage systems (KJA) is thought to be related to the hydro-oceanographic dynamics such as current conditions and water temperatures (Adibrata et al, 2020). The weaker water currents and the lower the water temperature can increase ectoparasites against fish in floating cage, this is certainly very detrimental to grouper fish farmers.…”
Section: Resultsmentioning
confidence: 99%
“…menyebabkan abnormalitas pada ikan antara lain insang berwarna pucat, bernafas lebih cepat dan overculum selalu terbuka. Hasil penelitian dilaporkan bahwa parasit ini tergolong berbahaya dalam budidaya kerapu cantang (Epinephelus fuscoguttatuslanceolatus) seperti yang terjadi di pantai timur Pangandaran, prevalensi mencapai 66,6% dan ikan dipelihara di KJA tradisional mencapai 44,4% disebabkan parasit Diplectanum (Adibrata et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Ectoparasites are one of the most common diseases that often attack tilapia (Irwandi et al, 2017). The ectoparasites Melanie et al (2022) usually attach to the outer body part or gill of the fish, inhibiting their growth and even resulting in mortality (Adibrata et al, 2020). The types of parasites that commonly attack tilapia include Trichodina sp., Dactylogyrus sp., Gyrodactylus sp., Argulus sp., Steinernema sp., and Epistylis sp.…”
Section: Introductionmentioning
confidence: 99%